Faktor Yang Mempengaruhi Tax Aggressiveness: Bagaimana Pengaruh Board Gender Diversity? - Anggelina, Bella; Trisnawati, Estralita; Firmansyah, Amrie (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p07, 2022)
This study aims to analyze the effect of audit quality, size of the board of directors, and capital intensity on tax aggressiveness with gender diversity of directors as a moderating variable. The research was conducted on mining companies based on the IDX-IC classification on the IDX for 4 years, 2016-2019 period. The sample obtained was 47 observations with cross-sectional data method and multiple linear regression test. The results show that audit quality is negatively related to tax aggressiveness, capital intensity is positively related to tax aggressiveness, and gender diversity of directors weakens the positive effect of capital intensity on tax aggressiveness. Keywords: Tax Aggressiveness; Capital Intensity; Board Gender Diversity; Audit Quality; Board Size.